Strategi Bertahan Usaha Mikro Kuliner pada Era Pandemic (Covid19) Ditinjau dari Sudut Pandang Ekonomi Syariah - Guraida, Guraida; Izmuddin, Iiz (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The general objective to be achieved in this research is to find out the strategies used by Micro Business actors in culinary deposits so that they can survive in the midst of the Pandemic from a sharia economic point of view. This research is a qualitative field research. By using primary data and secondary data. The analytical method used is a descriptive approach, namely identifying various problems faced by the culinary sector Micro Enterprises and analyzing them using SWOT/TOWS (IFE, EFE and IE) analysis, TOWS Matrix Analysis, SWOT Weight Tables. then formulate strategies to overcome them. The method of data collection in this study is by observation, interviews and documentation. The sample method uses snowball sampling. The results of the study found that in order to survive the pandemic, Micro-Entrepreneurs in the culinary sector of the city of Bukittinggi. Based on internal and external analysis, it can be found that the main strategy is the ST strategy (Strengts and Threats) with a total score of 5.35. Bukittinggi survives the pandemic era by using the ST strategy, which is to take advantage of strengths to overcome existing threats (Covid19). Meanwhile, from a sharia economic point of view, the overall strategy for implementing sharia economic principles in business is still not optimal for micro-enterprises. Keywords: Covid19, Strategic Management, Marketing, Micro Enterprises, Sharia Economics